Diffusion in Metals and Intermetallics: An Overview - Mehrer, Helmut (Diffusion Fundamentals, 2022)
After a few remarks about the history of diffusion in solids we remind the reader to some basics of diffusion such as tracer diffusion, interdiffusion, high-diffusivity paths, and basic diffusion mechanism in solids. We then summarize self-diffusion in cubic, hexagonal metals and metals with phase transformations. Then we summarize diffusion of substitutional impurities (solutes) in metals and remind the reader to the phenomena of slow solute diffusion in aluminium and of fast solute diffusion in polyvalent metals. We finish the part on solute diffusion with some remarks on interstitial impurities We start the part on intermetallic alloys by reminding the reader to some of the more frequent structures. We consider examples of the influence of order-disorder transformation on diffusion. We then discuss diffusion in cubic B2-structured phases and in B2-, L12- and DO3- intermetallics, We then discuss uniaxial L10-intermetallics and C11b-structured molybdenum disilicide. We finish with some remarks diffusion in the cubic Laves phase Co2Nb.